Applying quality to R&D means 'Learn-As-You-Go' - Eidt, Clarence M. Jr.
Clarence M. Eidt, Jr. relates how Exxon Research and Engineering Co. has obtained a continuous improvement in its R&D performance by applying the principles of quality management.
Exxon Research and Engineering Co. is convinced that-over time-Quality can provide a solid, sound approach to continuous improvement in R&D performance.
Quality principles, initially applied to the product and manufacturing process sectors, are being increasingly applied to less tangible activities such as administration and services. R&D is the latest frontier; and experience to date suggests this is still a virgin, pioneering field. Some characteristics of R&D make it a natural for Quality; others require careful tailoring and customizing of basic Quality principles to assure success. While there is no doubt that Quality basics apply to R&D, rigid application of manufacturing-derived concepts and training approaches has met with mixed results. A better approach is to position Quality principles in terms and trappings relevant to researchers by custom-designing training materials and work exercises to recognize unique R&D characteristics. This is how the Exxon Research and Engineering Company has attempted to introduce Quality into R&D.